ЧЕШКИТЕ ФРАЗЕМИ СО КОМПОНЕНТА NOHA / НОГА ВО ПРЕВОДИТЕ НА МАКЕДОНСКИ ЈАЗИК (Philological Studies, 2019)
The terms for the parts of the human body (based on metaphoric or metonymic meanings) are used daily to express a great number of things, while the body is used for counting (fingers) and as a means to determine a quantity or measure (measures of distance as foot, thumb, elbow, step, handful, sip, bite). The subject of this paper are phrases with a key somatic component LEG in the Czech works translated into Macedonian. We analyse the phrases on the basis of the body principle and according to the conceptual metaphors of Lаkoff and Johnson. Each scheme is analysed through specifics and characteristics found in the phrases, as well as the reality they interpret and evaluate. In the material excerpted from Czech works translated into Macedonian, we have come across 13 phrases having as a key component LEG.
Keywords: somatic phraseology, Macedonian language, Czech language, cognitivism